2018
DOI: 10.1038/s41598-018-26869-5
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed porous polyamide macrocapsule combined with alginate microcapsules for safer cell-based therapies

Abstract: Cell microencapsulation is an attractive strategy for cell-based therapies that allows the implantation of genetically engineered cells and the continuous delivery of de novo produced therapeutic products. However, the establishment of a way to retrieve the implanted encapsulated cells in case the treatment needs to be halted or when cells need to be renewed is still a big challenge. The combination of micro and macroencapsulation approaches could provide the requirements to achieve a proper immunoisolation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…In the present study, we therefore used a high-throughput, reproducible, and scalable co-axial airflow technique to conformally encapsulate islets and MSCs with an ultrapure formulation of alginate. Given that the alginate capsule is semi-permeable and thin (i.e., conformal coating ranges from 50 to 100 μm [ 14 , 15 ]), it will allow nutrients, oxygen, and glucose to diffuse to islets while concurrently enabling waste products to diffuse away from islets [ 16 ]. Furthermore, it also provides a physical barrier around islets to protect them from any immune mediated attack [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we therefore used a high-throughput, reproducible, and scalable co-axial airflow technique to conformally encapsulate islets and MSCs with an ultrapure formulation of alginate. Given that the alginate capsule is semi-permeable and thin (i.e., conformal coating ranges from 50 to 100 μm [ 14 , 15 ]), it will allow nutrients, oxygen, and glucose to diffuse to islets while concurrently enabling waste products to diffuse away from islets [ 16 ]. Furthermore, it also provides a physical barrier around islets to protect them from any immune mediated attack [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 3D printing of nylon 645 for knee implants 74 and nylon resin discs as scaffolds 75 was successfully accomplished. Non‐implant‐based applications like the printing of encapsulated alginate in PA microcapsules have also been reported to be feasible via SLS 76 ; through this technology, the fabrication of micro or nano‐sized capsules with a fixed amount of drugs for future drug delivery applications is obtained. In addition, the feasibility of the production of nylon 11 nanocomposite via SLS has been reported 77 .…”
Section: D Printing For Manufacturing Of Biomedical Devicesmentioning
confidence: 99%
“…Powder bed 3D-printing process enables the fabrication of drug delivery systems with arbitrary composition, geometries and shapes that could be tuned to control the drug release profile [ 187 , 188 , 189 , 190 ]. An interesting cell encapsulation device was fabricated using SLS 3D printing [ 191 ]. A patterned macrocapsule with smallest feature ranging from 0.5 mm to 1 mm was 3D-printed by SLS to encapsulate cell-containing microcapsules for cell-based therapy.…”
Section: Powder-based 3d Printing For Fabricating Devices With Micmentioning
confidence: 99%